Federalism and corporatism : on the approaches of policy-making and governance in the dual apprenticeship system in Germany and their functioning today - Kuhlee, Dina [Verfasser] (My University, 2015)
"Compared with England, where new implementations and programmes in the education system are often introduced at a striking pace, the German education system seems to be rather stable in its features and less dynamic in terms of reform and change. Hence, a phenomenon called 'reform bottleneck' (Reformstau) has often been observed. This also applies to the field of Vocational Education and Training (VET), where the dual apprenticeship system with its traditional structural characteristics is still the central institution to prepare young people for work and employment. Although fundamental changes in the system as a result of sudden reform processes have not happened in recent decades, subtle developments have influenced the German VET system and its functioning. The specific legal and institutional construction of the dual apprenticeship system with its two main and interrelated features, federalism and corporatism, is the backbone of the specific approaches of policy-making and governance in German VET. This paper provides an overview of the institutional and legal characteristics of the dual apprenticeship system and discusses the associated approaches of policy-making and governance. Considering the different responsibilities of the public and the private sphere, contextual features of the labour market and of the school system, the paper analyses political reform initiatives, changing stakeholder interests and configurations (in particular of the so-called social partners), and their relevance for the functioning and development of the German dual apprenticeship system." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; Duales System; Berufsbildungspolitik; Bildungsreform; Bildungssteuerung; Föderalismus; Korporatismus; Sozialpartner